(untitled) (Research, Society and Development, 2022)
This study aims to map and identify educational health technologies that aim to adopt behaviors related to healthy lifestyles in young adolescents. The integrative literature review method was used to search for evidence around the search question involving controlled terms for identification in the selected databases. 1488 references were found in the initial stage: Scopus=363; Web of Science=320; CINAHL=238; Eric=211; MEDLINE/PubMed=159; LILACS=126; BDENF=31; IBECS=40. After the screening and matched search process, 23 studies that met the inclusion criteria were included. Information was extracted on the country of origin, language, type of study, collection instruments, type of technology, theory used to support the intervention, and duration. There was a greater predominance of studies developed in Spain, and, in relation to the duration of applicability, 10 studies (43.4%) were carried out in 12 months or more. Intervention strategies focusing on the whole school and multiple dimensions of lifestyle were the most used among the studies found (10), followed by smartphone apps that were used in (07) studies. Despite the description of the interventions, it was not possible to consistently identify the adherence of new behaviors, only participants’ reports, which is one of the challenges of monitoring the effectiveness of interventions. The involvement and participation of young people in the construction phases were decisive for greater engagement and interaction in the activities proposed by the interventions, which may indicate paths for the construction of new technologies.